Epidemiological Profile of Congenital Heart Disease in a National Referral Hospital - Muhamad Taufik Ismail; Fera Hidayati; Lucia Krisdinarti; Noormanto Noormanto; Sasmito Nugroho; Abdul Samik Wahab (ACI (Acta Cardiologia Indonesiana), 2015)
Introduction: Sardjito Hospital is the tertiary referral hospital in Yogyakarta and Central Java, Indonesia. There are no reported data measuring epidemiological profi le of congenital heart disease (CHD) in this region. This study was aimed specifi cally to determine the most major lesion and type of CHD in one of an over-populated area in Indonesia. Methods: The retrospective observational study was conducted during January 2014 to December 2014 in Sardjito Hospital. In and outpatients with CHD taken from medical record were noted their clinical data and only patients with transthoracal echocardiographic proof of CHD were included in this study. CHD with more than single lesion was simplifi ed as one lesion which had most major impact on hemodynamic circulation. The denomerator was the sum of all new patients visiting to the hospital at 2014. Data were entered in MS-excel and analyzed by software SPSS version 22.Results: We had total 650 new patients with CHD registered to Sardjito Hospital in 2014. The incidence of CHD was 134/10.000 person-years consisted of adult 22% and children 78% (female 60% and male 40%). Ventricle septal defect (VSD) was the most common lesion among children (30%) followed by atrial septal defect (ASD) 17%, persistent ductus arteriosus (PDA) 16%, andTetralogy of Fallot (TOF) 7%. Meanwhile in adult, ASD was the most frequent CHD (60%), continued by VSD 23%, TOF 8%, and PDA 4%. Secundum, primum, and sinus venosus type were found in 94%, 3%, and 3% of total ASD in children, and 99%, 1%, and 0% of adult respectively. Perimembran outlet (PMO), doubly committed subarterial (DCSA), and inlet were found in 66%, 12%, and 12% of total VSD in children, and 39%, 54%, and 0% of adult respectively. TOF had the highest incidence of cyanotic heart diseases (33 cases, 7%) in children and also in adult (12 cases, 8%). Conclusion: The incidence of CHD was 134/10.000 person-years. The most common lesion among children was VSD and in adult was an ASD. TOF had the highest incidence of cyanotic heart disease among children and adult. Secundum type was the most common fi nding in all ages of ASD population, whereas PMO and DCSA were the most frequent type of VSD in children and adult respectively.Keywords: incidence, congenital heart disease, hospital, cyanotic, type